2008
DOI: 10.1111/j.1601-5223.1988.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative fertility and mutation rate in neurofibromatosis

Abstract: The epidemiology and genetics of neurofibromatosis were described in a previously published population study. The present paper supplements that investigation with an estimation of mutation rate and relative fertility, or selection disadvantage, of neurofibromatosis. The relative fertility was estimated to be 78 % and the mutation rate was found to be somewhere between 2.4 and 4.3xThe results verify that this common disease has one of the highest mutation frequencies known in man.Hans Olof Akesson, Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…A 1988 study of all individuals with "neurofibromatosis" in Gothenburg, Sweden found a reduction in fertility by~20% and ascribed the difference to social rather than biologic factors. 113 There are limited data on the safety of oral or depot contraceptives in women with NF1. However, the prevention of unintended pregnancy is important, and thus the benefits likely outweigh any theoretical concerns.…”
Section: Contraception Pregnancy and Assisted Fertilitymentioning
confidence: 99%
“…A 1988 study of all individuals with "neurofibromatosis" in Gothenburg, Sweden found a reduction in fertility by~20% and ascribed the difference to social rather than biologic factors. 113 There are limited data on the safety of oral or depot contraceptives in women with NF1. However, the prevention of unintended pregnancy is important, and thus the benefits likely outweigh any theoretical concerns.…”
Section: Contraception Pregnancy and Assisted Fertilitymentioning
confidence: 99%
“…In a study of young adults, Garty, Laor, and Danon (1994) reported that the IQ scores of 17-year-old Israeli military recruits with NF-1 were not significantly lower than those of the non-NF-1 recruits once the scores were corrected for gender and ethnic origin. Researchers in Sweden undertook an extensive evaluation of NF-1 in the city of Gothenburg (Samuelsson & Akesson, 1989;Samuelsson & Riccardi, 1989a, 1989b. The study examined intelligence in 71 patients, all 20 years of age or older.…”
Section: Cognitive Correlates Of Nf-1 In Adultsmentioning
confidence: 99%
“…Despite reproductive fitness being reduced in individuals with NF1 [2–4, 6], gonadal function has not been well characterized. Delayed puberty [9] and early menopause [11] suggest that reproductive function may be altered in people with NF1.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with NF1 have fewer children, on average, than individuals in the general population, and this reduction in fertility is greater in males than females [2–6]. This reduction in reproductive fitness has been attributed to social rather than biological factors [2, 4], but gonadal function has rarely been examined in patients with NF1. One, German study [7] found decreased libido in males with NF1 and one French study [8] described testicular dystrophy.…”
Section: Introductionmentioning
confidence: 99%